A hadith about riba and the relationship with occupation : Which one is preferable between merchant and islamic bank clerk? - Kafabih, An'im; Manzilati, Asfi (Journal of Islamic Economics Lariba, 2018)
This study examines what provides the lowest relation to interest rates between traders who discuss and load their merchandise once exemplified by the Prophet Muhammad, and employees of Islamic banks. This study is necessary because the Prophet Muhammad once said at the end of time, there will be a time when people will accept usury, while someone rejects it, then these people will use the dust. This study uses a quantitative approach, the smallest square of the regression model that supports this study. From the results of the existing research on the statistics of bank employees, in this case, it is reflected in the BSM employee's work which describes the relationship to lower interest rates of large traders who obtain and buy their merchandise.